CONSUMER SATISFACTION AND CUSTOMER LOYALTY IN THE SERVICES SECTOR: A CASE STUDY OF BKT BANK- PRISHTINA, KOSOVO - Ismajli, Ali; Hysi - Panajoti, Vjollca; Fejza, Labeat E.; Ismajli, Diellza A.; Fejza, Ejup (European Scientific Journal, ESJ, 2014)
Consumer behavior is the study of the way people, groups and organizations select, buy, use products, services, ideas or experiences in order to satisfy their needs and desires, while customer loyalty express the level of loyalty customer have to the company he/she buy products or services. Therefore, these two concepts are strongly interrelated. The consumer tends to be loyal to producer or service provider as long as the consumer is satisfied with the products or services they offer. The aim of this paper is to analyze and present consumer satisfaction and loyalty of customers of Banka Kombëtare Tregtare-BKT, branches in Prishtina, Republic of Kosovo. During the research process, we used both secondary and primary data. For the sake of research, we have interviewed 200 customers who are using products/services offered by BKT-branches in Prishtina, Capital of the Republic of Kosovo. Random customers were used in this survey and questions asked were closed type ones. The research instrument used in this study was a questionnaire while the technique used was through direct communication. The research was conducted between May and July 2012.